P378Variant rs2200733 on chromosome 4q25 independently confers increased risk of atrial fibrillation in a greek population. (15th July 2014) - Kalinderi, K; Fragakis, N; Koskinas, KC; Katritsis, D; Letsas, K; Efremidis, M; Rossios, K; Skeberis, V; Vassilikos, V; Fidani, L
Abstract: Aims: Atrial fibrillation (AF) is a common arrhythmia with evidence of genetic susceptibility. The rs2200733 single-nucleotide polymorphism (SNP) in a noncoding region on chromosome 4q25 has been associated with AF. The purpose of this case-control study was to determine the distribution of the rs2200733 polymorphism in a Greek population with AF. Methods: All individuals included in our study, were genotyped for the presence of the rs2200733 using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLPs) method. Results: A total of 295 subjects of Greek origin, 167 AF patients and 128 controls were included in the study. Patients with AF were less often male, had a lower incidence of coronary artery disease, and had larger left atria diameter (LA) diameter compared to controls. The T/T genotype and the T allele were detected more frequently in patients with AF compared to controls (13.2% vs. 2.3%, p=0.001 and 29.6% vs. 17.9%; p=0.001). T/T genotype and LA diameter were the only independent predictors of AF (OR 1.74, 95% CI: 1.40-2.98; p=0.005 and OR 2.88, 95% CI: 1.83-5.62; p<0.001, respectively). A trend of association was observed between the T/T genotype and lone AF (p=0.08). Conclusion: Our results suggest that SNP rs2200733 confers a significant risk of AF in a Greek population, providing further support to the previously reported association between AF and rs2200733 polymorphism on chromosome 4q25.